Employment in call centres in Bulgaria. (1st July 2009) - Vassil Kirov; Kapka Mircheva
Abstract : In recent years, Bulgaria has become an important destination for call-centre outsourcing of client services from abroad. Thousands of new jobs in call centres have been created in the capital and the largest Bulgarian cities. This remarkable development has not yet been a subject of serious analysis. For this reason this article aims to present a summary of the development of the call-centre industry in Bulgaria, focusing on employment in the sector. In particular, the authors, focus on the characteristics of the workers who are sought, recruitment policies and training in call centres, working environments, remuneration practices and workplace representation of employees. The analysis makes it possible to draw some conclusions about the characteristics of employment in call centres in Bulgaria and how this compares with employment in the sector in other countries.